2019
DOI: 10.1177/2045894018823715
|View full text |Cite
|
Sign up to set email alerts
|

Riociguat improves health‐related quality of life for patients with pulmonary arterial hypertension: results from the phase 4 MOTION study

Abstract: Pulmonary arterial hypertension (PAH) is characterized by progressive dyspnea and exercise limitation and is associated with reduced health-related quality of life. Few clinical studies have evaluated the primary effects of treatment of PAH from the patient perspective. Here, we present the impact of riociguat on patient-reported outcomes (PROs) in treatment-naïve patients with PAH. MOTION (NCT02191137) was an open-label, phase 4 trial of riociguat monotherapy in treatment-naïve patients with PAH. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…A phase IV, prospective, single‐arm, open‐label study to measure outcome in patients with PAH not on active treatment ( MOTION ) …”
Section: Methodsmentioning
confidence: 99%
“…A phase IV, prospective, single‐arm, open‐label study to measure outcome in patients with PAH not on active treatment ( MOTION ) …”
Section: Methodsmentioning
confidence: 99%
“…The MOTION study (NCT02191137) was a prospective, multicentre, single‐arm, open‐label, phase IV study to assess the impact of riociguat on patient‐reported outcomes in patients with PAH 94 . The primary endpoint was change from baseline to Week 24 in the LPH questionnaire, a 21‐item, validated, disease‐specific health‐related quality of life assessment tool comprising physical (score 0–40) and emotional (score 0–25) domains; a reduction in score indicates an improvement in health‐related quality of life 95 .…”
Section: Further Studies In Pah and Ctephmentioning
confidence: 99%
“…The MOTION study (NCT02191137) was a prospective, multicentre, single‐arm, open‐label, phase IV study to assess the impact of riociguat on patient‐reported outcomes in patients with PAH. 94 The primary endpoint was change from baseline to Week 24 in the LPH questionnaire, a 21‐item, validated, disease‐specific health‐related quality of life assessment tool comprising physical (score 0–40) and emotional (score 0–25) domains; a reduction in score indicates an improvement in health‐related quality of life. 95 The primary endpoint was met, with a mean ± SD change in LPH score from baseline to Week 24 of −5.4 ± 27.8 ( n = 75, P = .048; the minimally important difference that indicates a clinically meaningful improvement was estimated to be a change from baseline of 7).…”
Section: Further Studies In Pah and Ctephmentioning
confidence: 99%
“…Несмотря на то, что в данном post-hoc-анализе отмечался положительный результат, следует помнить, что риоцигуат не зарегистрирован по показанию ЛАГ-ВПС. Для уверенности в эффективности и безопасности риоцигуата у данной подгруппы пациентов необходимы дальнейшие исследования [12,16] [17].…”
Section: ðèîöèãóàò ïðè ëàãunclassified